2019
DOI: 10.1177/0042098019853480
|View full text |Cite
|
Sign up to set email alerts
|

The ‘reverse bamboo network’: Sociocultural dialectics of China’s FDI in housing (FDIH) in Iskandar Malaysia

Abstract: The ‘bamboo network’ is used to conceptualise the investment flow into China from the Chinese diaspora, particularly those who resided in South-east Asia. However, global economic events have decimated the wealth of overseas Chinese whilst mainland Chinese businesses prospered, resulting in what is now reimagined as the ‘reverse bamboo network’. In Iskandar Malaysia (IM), which is a transnational economic region bordering Singapore, the foreign direct investment in housing (FDIH) from China has surpassed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…As discussed, many members of the Chinese diaspora act as global real estate intermediaries, leveraging their bilingual abilities and understanding of cross-cultural contexts to disseminate information and facilitate capital flows across networks (Ley, 2017; Wong, 2017a). The overseas Chinese community can thus serve as an important investment mediator (Hamzah, 2019; Karreman et al, 2017) and source of capital, too. Thus, the relationship between overseas Chinese communities and Chinese real estate developers cannot be ignored in Mainland Chinese FDIRE, especially when led by PEs.…”
Section: Empirical Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As discussed, many members of the Chinese diaspora act as global real estate intermediaries, leveraging their bilingual abilities and understanding of cross-cultural contexts to disseminate information and facilitate capital flows across networks (Ley, 2017; Wong, 2017a). The overseas Chinese community can thus serve as an important investment mediator (Hamzah, 2019; Karreman et al, 2017) and source of capital, too. Thus, the relationship between overseas Chinese communities and Chinese real estate developers cannot be ignored in Mainland Chinese FDIRE, especially when led by PEs.…”
Section: Empirical Results and Discussionmentioning
confidence: 99%
“…Co-ethnic ties can serve as mediating tools for investors to help reduce their business risks and decrease transaction costs, as well as to overcome cultural and linguistic barriers in order to more efficiently obtain place-specific information (Filatotchev et al, 2011; Gao et al, 2013; Ho, 2020; King, 2012). These mediators also help lower other institutionalized barriers such as unfamiliar legal frameworks and issues managing local employees (Hamzah, 2019; Smart and Hsu, 2004). Consequently, ethnic Chinese networks promote flows of Chinese property capital, which in turn facilitates the mobility and wealth accumulation of overseas Chinese communities.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Within Chinese society, interpersonal networks and reciprocity, or a form of social ties known as guanxi, play an important role that extends to the business world (Hsu & Saxenian, 2000;Liang et al, 2019). Several studies explore how overseas Chinese communities facilitate China's outbound investments through guanxi social networks (Hamzah, 2020;Javorcik et al, 2011;Karreman et al, 2017). Overseas Chinese communities can assist Chinese MNEs in reducing their business risks and decreasing transaction costs, as well as helping them more efficiently obtain place-specific information (Filatotchev et al, 2011;Gao et al, 2013;King, 2012).…”
Section: Chinese Migrant Network and Guanxi Capitalismmentioning
confidence: 99%
“…Recent research within relational economic geography, however, has demonstrated that factors within host countries such as the presence of overseas Chinese communities are also important in facilitating OFDI. Ethnicity‐based networks act as nodes of knowledge and information exchange, assisting Chinese MNCs to reduce communication barriers and obtain local knowledge (Deng et al., 2020; Hamzah, 2020; Karreman et al., 2017; Liang et al., 2019). Their presence, especially in new overseas markets, may be particularly important to helping PEs and smaller SOEs gain footholds.…”
Section: Introductionmentioning
confidence: 99%